Fearless and free ebook A memoir. - Baker, Josephine (2025)
A MOST ANTICIPATED BOOK OF THE YEAR: The TODAY Show, Vanity Fair, Financial Times , W Magazine, Oprah Daily, LibraryReads Praised as “funny and witty” by Kwame Alexander on the TODAY show, now published in the US for the first time, Fearless and Free is the memoir of the “trailblazing” ( People ), rule-breaking, one-of-a-kind Josephine Baker, the iconic dancer, singer, spy, and Civil Rights activist . “A gorgeous, captivating gem of a memoir… Josephine Baker’s as enthralling on the page as she was on the stage.” —Abbott Kahler, New York Times bestselling author of Eden Undone and Sin in the Second City After stealing the spotlight as a teenaged Broadway performer during the height of the Harlem Renaissance, Josephine then took Paris by storm, dazzling audiences across the Roaring Twenties. In her famous banana skirt, she enraptured royalty and countless fans—Ernest Hemingway and Pablo Picasso among them. She strolled the streets of Paris with her pet cheetah wearing a diamond collar. With her signature flapper bob and enthralling dance moves, she was one of the most recognizable women in the world. When World War II broke out, Josephine became a decorated spy for the French Résistance. Her celebrity worked as her cover, as she hid spies in her entourage and secret messages in her costumes as she traveled. She later joined the Civil Rights movement in the US, boycotting segregated concert venues, and speaking at the March on Washington alongside Martin Luther King Jr. First published in France in 1949, her memoir will now finally be published in English. At last we can hear Josephine in her own voice: charming, passionate, and brave. Her words are thrilling and intimate, like she’s talking with her friends over after-show drinks in her dressing room. Through her own telling, we come to know a woman who danced to the top of the world and left her unforgettable mark on it.